Agritourism around the globe: Definitions, authenticity, and potential controversy - R. David Lamie; Lisa Chase; Emilio Chiodo; Lori Dickes; Sharon Flanigan; Claudia Schmidt; Thomas Streifeneder (Journal of Agriculture, Food Systems, and Community Development, 2021)
This commentary identifies the variability in definitions of agritourism that exists in a variety of different countries, discusses reasons why this variability might produce problems, and provides examples of efforts to harmonize these definitions, including an ongoing international dialogue on the topic.